Proposições teórico-práticas de acessibilidade comunicativa na formação de jornalistas - Wobeto, Samara Letícia (2025)
This dissertation aims to problematize the inclusion of communicative accessibility in the pedagogical practices of journalism teaching. The issues surrounding accessibility in communication and journalism are broad and complex, and constitute a gap. Firstly, because the media representation of people with disabilities is, for the most part, ableist, through the reproduction of stereotypes of overcoming and pity. Secondly, there are few accessible narratives, in which journalistic products are built with assistive technologies that allow people with disabilities to be autonomous consumers of information. There are also few that are in production - and even in the university environment. In studies such as those by Bonito (2015), Beraldo (2021) and Wobeto (2023), the issue of education remained a concern. This would be a possible space for changing professional culture, because it is also the place where new journalists are trained. This raises the problem of this dissertation, based on the following question: How can communicative accessibility be problematized and included in the pedagogical practices of journalism teaching? In order to achieve the proposed objective, the specific objectives are: a) To map pedagogical initiatives that work on accessibility in Journalism courses; b) To experiment, within the scope of Guided Teaching, with ways of inserting communicative accessibility into Journalism teaching; c) To understand the insertion of pedagogical practices - theoretical and practical - on communicative accessibility in Journalism courses; and d) To propose pedagogical practices of communicative accessibility in Journalism courses. The methodology comprises six phases, which are not necessarily linear and temporal: 1) literature review and state of the art (Barichello, 2016), to set up the theoretical frame of reference; 2) documentary analysis (Moreira, 2009) of pedagogical projects, syllabuses and curricular matrices of Journalism courses at Brazilian federal universities; and structured interviews (Duarte, 2010) with the courses; 3) participant research (Peruzzo, 2010; Martino, 2018) in conjunction with observation (Gil, 2008) and the field diary (Winkin, 1998) - through mentored teaching; combined with structured interviews (Duarte, 2010); 4) semi-structured interviews (Duarte, 2010) with the teachers of the initiatives mapped in the documentary analysis; 5) the analytical phase, which involves transcribing and organizing the data; and 6) writing, qualifying and defending the dissertation. The results point to the proposal's potential, both for raising awareness among students and building accessibility as a professional precept, and for the relationship between research and teaching that permeates existing initiatives. The proposals are based on the relationship between theory and practice, between action and reflection, and based on Freirean pedagogy for teaching journalism.